From Clinical Practice Guidelines to Computer-interpretable Guidelines - Latoszek-Berendsen, A.; Tange, H.; van den Herik, H. J.; Hasman, A. (Methods of Information in Medicine, 2010)
Background: Guidelines are among us for over 30 years. Initially they were used as algorithmic protocols by nurses and other ancillary personnel. Many physicians regarded the use of guidelines as cookbook medicine. However, quality and patient safety issues have changed the attitude towards guidelines. Implementing formalized guidelines in a decision support system with an interface to an electronic patient record (EPR) makes the application of guidelines more personal and therefore acceptable at the moment of care.Objective: To obtain, via a literature review, an insight into factors that influence the design and implementation of guidelines.Methods: An extensive search of the scientific literature in PubMed was carried out with a focus on guideline characteristics, guideline development and implementation, and guideline dissemination.Results: We present studies that enable us to explain the characteristics of high-quality guidelines, and new advanced methods for guideline formalization, computerization, and implementation. We show how the guidelines affect processes of care and the patient outcome. We discuss the reasons of low guideline adherence as presented in the literature and comment upon them.Conclusions: Developing high-quality guidelines requires a skilled team of people and sufficient budget. The guidelines should give personalized advice. Computer-interpretable guidelines (CIGs) that have access to the patient’s EPR are able to give personal advice. Because of the costs, sharing of CIGs is a critical requirement for guideline development, dissemination, and implementation. Until now this is hardly possible, because of the many models in use. However, some solutions have been proposed. For instance, a standardized terminology should be imposed so that the terms in guidelines can be matched with terms in an EPR. Also, a dissemination model for easy updating of guidelines should be established. The recommendations should be based on evidence instead of on consensus. To test the quality of the guideline, appraisal instruments should be used to assess the guideline as a whole, as well as checking the quality of the recommendations individually. Only in this way optimal guideline advice can be given on an individual basis at a reasonable cost.
Keywords: Clinical practice guidelines; paper-based guidelines; computer-based guidelines; computerized (clinical) guidelines; computerinterpretable guidelines; guideline formalization; decision support system